SOCIAL MOBILITY IN THE PURSUIT OF HAPPYNESS (2006): A SOCIOLOGICAL PERSPECTIVE - Abdullah, Nabilah Rona (ELite Journal : International Journal of Education, Language and Literature, 2025)
The Pursuit of Happiness is a biopic film released in 2006 and directed by Gabriele Muccino. The film depicts social mobility and various issues related to a stratified society. This study examines how Chris Gardner embodied social mobility and the factors behind it. The data was derived from monologues, dialogues, and narrative segments in film scripts. Furthermore, the analysis employed the close reading method alongside Sorokin’s theory of social mobility as articulated in “Social and Cultural Mobility” (1959). The findings portrayed how Chris Gardner’s experience embodies social mobility, particularly upward mobility. This can be observed by his shift from a lower class (homelessness, financial instability, and unpaid internships) to an upper class (securing a permanent position as a stockbroker and successfully founding his own stock company). Moreover, the causes of this upward mobility include an environmental change (entering the stockbroker profession), differences between parents and their children (variations in characteristics between Chris and his parents), and defective social distribution (possessing talents and abilities confined to the upper classes).